Specific post-translational modifications of soluble tau protein distinguishes Alzheimer’s disease and primary tauopathies - Nathalie Kyalu Ngoie Zola; Clémence Balty; Sébastien Pyr dit Ruys; Axelle A. T. Vanparys; Nicolas D. G. Huyghe; Gaëtan Herinckx; Manuel Johanns; Emilien Boyer; Pascal Kienlen-Campard; Mark H. Rider; Didier Vertommen; Bernard J. Hanseeuw (Nature Communications, 2023)
Abstract Tau protein aggregates in several neurodegenerative disorders, referred to as tauopathies. The tau isoforms observed in post mortem human brain aggregates is used to classify tauopathies. However, distinguishing tauopathies ante mortem remains challenging, potentially due to differences between insoluble tau in aggregates and soluble tau in body fluids. Here, we demonstrated that tau isoforms differ between tauopathies in insoluble aggregates, but not in soluble brain extracts. We therefore characterized post-translational modifications of both the aggregated and the soluble tau protein obtained from post mortem human brain tissue of patients with Alzheimer’s disease, cortico-basal degeneration, Pick’s disease, and frontotemporal lobe degeneration. We found specific soluble signatures for each tauopathy and its specific aggregated tau isoforms: including ubiquitination on Lysine 369 for cortico-basal degeneration and acetylation on Lysine 311 for Pick’s disease. These findings provide potential targets for future development of fluid-based biomarker assays able to distinguish tauopathies in vivo.